Role of Intravenous Dexmedetomidine as an Adjuvant in Labour Analgesia in Pre-eclampsia: A Prospective Study - Jyothsna C; Roopa Kotha (Academia Anesthesiologica International, 2020)
Background: Dexmedetomidine is a highly selective ?-2 adrenergic receptor agonist with several diverse actions like sedation, anxiolysis, sympatholysis, analgesia, and decreased intraoperative anesthetic requirements (narcotic, inhalational). Intravenous (IV) dexmedetomidine can be used as an adjuvant in labour analgesia in preeclampsia patients as onset is faster and duration of analgesia is longer. Aim of the study: The aim of the study was to determine the role of intravenous Dexmedetomidine as an adjuvant in Labour analgesia in PIH.Subjects and Methods:This was a prospective study and was done in the department of Anaesthesia at Maheshwara Medical College. Our study included 60 full term pregnant women with preeclampsia, within 25 to 45 years age range. They were divided into two groups, as Test group and Control group of 30 patients each. Test group received IV Dexmedetomidine and Control group received IV Fentanyl.Results:Maximum number of cases 15/30 (50%) were in the age group 31-35 years, Majority were primigravida ie, 60% ( 36/60). Onset of analgesia was faster, duration of analgesia was longer and uterine contraction was greater with IV Dexmedetomidine as compared to IV fentanyl.Conclusion:From the present study we conclude that IV Dexmedetomidine can be used for labour analgesia in pregnant women with preecampsia and observed that onset and duration of analgesia are better and also it gives stable maternal parameters of maternal heart rate and mean blood pressure.